Palladium-mediated heck-type reactions of [(Bromodifluoromethyl)sulfonyl] benzene: Synthesis of α-alkenyl- and α-heteroaryl-substituted α,α-difluoromethyl phenyl sulfones - Nakin Surapanich (2018)
Palladium-catalyzed Heck-type reactions of [(bromodifluoromethyl)sulfonyl] benzene (1) with styrene derivatives and heteroaromatic compounds successfully gave α-alkenyl- and α-heteroaryl-substituted α,α- difluoromethyl phenyl sulfones, respectively. Palladium-catalyzed Heck-type reactions of [(bromodifluoromethyl)sulfonyl] benzene (1) are reported. Both styrene derivatives and heteroaromatic compounds gave PhSO 2 CF 2 -substituted products in moderate to good yields. © 2012 2012 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.